Evaluation of Solubility, and Volumetric and Morphological Alterations of Bioceramic Filling Material for Primary Teeth: A New Methodological Approach - Víctor M. Ochoa-Rodríguez; Hernán Coaguila-Llerena; Leandro Fernandes; Ana B. B. Solcia; Juliane M. Guerreiro-Tanomaru; Mário Tanomaru-Filho; Gisele Faria (International Journal of Dentistry)
Objective. To evaluate the solubility and the volumetric and morphological alterations of bioceramic filling material (Bio-CP) for primary teeth. Materials and Methods. Bio-CP, Calen thickened with zinc oxide (Calen-ZO), and with zinc oxide eugenol (ZOE) were placed in 1- or 2-mm-diameter polyethylene tubes and immersed in water or phosphate-buffered saline (PBS) for 30 days. The solubility (mass loss) was assessed using methodology modified from ISO 6876. Filling capacity, volumetric changes, and presence of voids were assessed by microcomputed tomography (micro-CT). The surface distribution of the chemical elements and the crystalline phases was evaluated by energy scattering X-ray scanning electron microscopy (SEM-EDX) and X-ray diffraction (XRD) to detect hydroxyapatite precipitate and components. The Shapiro–Wilk, Kruskal–Wallis, and Dunn’s or two-way ANOVA and Tukey post hoc test were used (α = 0.05). Results. The solubility was ZOE > Calen-ZO = Bio-CP. Calen-ZO and Bio-CP were more soluble in water than in PBS. All the materials showed greater solubility in 2-mm tube diameter in both PBS and distilled water, except for Bio-CP in distilled water, which showed no difference between both tube diameters (1 and 2 mm). Only Calen-ZO and ZOE were analyzed by micro-CT, because Bio-CP separated into two phases during scanning. Calen-ZO had greater volumetric loss and presence of voids than ZOE in water, but there was no difference in PBS. The hydroxyapatite precipitate on the surface of Bio-CP and Calen-ZO was detected after immersion in PBS. Conclusion. Although Bio-CP had acceptable solubility and filling capacity, its composition did not allow a proper volumetric and void assessment. From a clinical perspective, Bio-CP has the potential to become a suitable material for root canal filling in primary teeth. Nonetheless, its composition must first be revised to achieve better chemical stability prior to its recommendation.